Comprehensive Insights into the Thermal Stability, Biodegradability, and Combustion Chemistry of Pyrrolidinium‐Based Ionic Liquids. Issue 15 (21st July 2017) - Eshetu, Gebrekidan Gebresilassie; Jeong, Sangsik; Pandard, Pascal; Lecocq, Amandine; Marlair, Guy; Passerini, Stefano
Abstract: The use of ionic liquids (ILs) as advanced electrolyte components in electrochemical energy‐storage devices is one of the most appealing and emerging options. However, although ILs are hailed as safer and eco‐friendly electrolytes, to overcome the limitations imposed by the highly volatile/combustible carbonate‐based electrolytes, full‐scale and precise appraisal of their overall safety levels under abuse conditions still needs to be fully addressed. With the aim of providing this level of information on the thermal and chemical stabilities, as well as actual fire hazards, herein, a detailed investigation of the short‐ and long‐term thermal stabilities, biodegradability, and combustion behavior of various pyrrolidinium‐based ILs, with different alkyl chain lengths, counteranions, and cations, as well as the effect of doping with lithium salts, is described. Abstract : Toxic combustion : Ionic liquids (ILs), as electrolyte components for high‐energy batteries, offer a series of advantages with respect to molecular, solvent‐based, conventional electrolytes. A detailed investigation of the short‐ and long‐term thermal stabilities, biodegradability, and combustion behavior of various pyrrolidinium‐based ILs, with different alkyl chain lengths, counteranions, and cations, is described.